1997
DOI: 10.1359/jbmr.1997.12.12.2014
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of an Osteocyte-like Cell Line, MLO-Y4

Abstract: Although osteocytes are the most abundant cells in bone, their functional role remains unclear. In part, this is due to lack of availability of osteocyte cell lines which can be studied in vitro. Since others have shown that cell lines can be readily developed from transgenic mice in which the SV40 large T-antigen oncogene is expressed under the control of a promoter which targets the cells of interest, we used this approach to develop an osteocyte cell line. We chose as a promoter osteocalcin, whose expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
377
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 483 publications
(393 citation statements)
references
References 41 publications
(45 reference statements)
5
377
0
4
Order By: Relevance
“…(28) Although Western blotting demonstrated that MLO-Y4 cells produce FGF23, mouse FGF23 migrated faster than human FGF23 and failed to show any processing to cFGF23, suggesting that in mice FGF23 may be differently processed. In addition, in spite of the fact that FGF23 could be detected by Western blot, it could not be detected by the intact FGF23 assay, which is known to detect mouse FGF23 (data not shown).…”
Section: Fgf23 Ppgalnact3 and Furin Gene Expressionmentioning
confidence: 98%
“…(28) Although Western blotting demonstrated that MLO-Y4 cells produce FGF23, mouse FGF23 migrated faster than human FGF23 and failed to show any processing to cFGF23, suggesting that in mice FGF23 may be differently processed. In addition, in spite of the fact that FGF23 could be detected by Western blot, it could not be detected by the intact FGF23 assay, which is known to detect mouse FGF23 (data not shown).…”
Section: Fgf23 Ppgalnact3 and Furin Gene Expressionmentioning
confidence: 98%
“…Establishment of a cell line, MLO-Y4, captured the imagination of many investigators who now had access to a osteocyte-like cell (Kato et al, 1997) to examine osteocytic response to mechanical loading in the form of shear stress, osteocyte apoptosis, osteocyte signaling, and osteocyte communication through gap junctions and hemichannels (Bonewald, 2007). Breakthroughs were made in the identification of important markers for osteocyte differentiation which included E11/gp38,an early marker for embedding cells, Phex and dentin matrix protein 1, DMP1, important in metabolism, and Sost/sclerostin, a late marker for mature osteocytes (Bonewald, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The murine long bone osteocyte Y4 (MLO-Y4) cell line (supplied from University of Missouri, Kanas City, USA) was used and cultured as previously described (36,37). Briefly, the cells were cultured on collagen-coated (rat tail type I collagen; BD Biosciences, Franklin Lakes, NJ, USA) plastic ware and were grown at 37˚C, 5% CO 2 , 95% air with α-minimal essential medium (α-MEM; 1X; Invitrogen; Thermo Fisher Scientific, Inc., Waltham, MA, USA) supplemented with 2.5% fetal bovine serum (FBS) (PAA; GE Healthcare Life Sciences, Pittsburgh, PA, USA), 2.5% bovine calf serum (BCS; GE Healthcare Life Sciences, Logan, UT, USA) and 100 U/ml penicillin/streptomycin at (Invitrogen; Thermo Fisher Scientific, Inc).…”
Section: Methodsmentioning
confidence: 99%